Descents in Noncrossing Trees - Hough, David S. (The Electronic Journal of Combinatorics, 2003)
The generating function for descents in noncrossing trees is found. A bijection shows combinatorially why the descent generating function with descents set equal to $2$ is the generating function for connected noncrossing graphs.